Beam energy dependence of jet-quenching effects in Au+Au collisions at √(sNN)= 7.7, 11.5, 14.5, 19.6, 27, 39, and 62.4 GeV - STAR Collaboration (Physical Review Letters, 2018)
We report measurements of the nuclear modification factor RCP for charged hadrons as well as identified π+(−), K+(−), and p(¯p) for Au+Au collision energies of √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, and 62.4 GeV. We observe a clear high-pT net suppression in central collisions at 62.4 GeV for charged hadrons which evolves smoothly to a large net enhancement at lower energies. This trend is driven by the evolution of the pion spectra but is also very similar for the kaon spectra. While the magnitude of the proton RCP at high pT does depend on the collision energy, neither the proton nor the antiproton RCP at high pT exhibit net suppression at any energy. A study of how the binary collision-scaled high-pT yield evolves with centrality reveals a nonmonotonic shape that is consistent with the idea that jet quenching is increasing faster than the combined phenomena that lead to enhancement.
30 citations (Crossref) [2023-10-31]
Keywords: Au+Au collisions; Beam energies; Binary collisions; Charged hadrons; Colliding beam accelerators; Collision energies; Fighter aircraft; Germanium compounds; Hadrons; Lower energies; Measurements of; Nuclear modification factors; Quenching; dept.phy; peer-reviewed